Design, Synthesis, Molecular Docking, and Tumor Resistance Reversal Activity Evaluation of Matrine Derivative with Thiophene Structure - Jinrui Wei; Yuehui Liang; Lichuan Wu (Molecules, 2021)
Nasopharyngeal carcinoma (NPC) frequently occurs in Southern China. The main treatments of NPC are chemotherapy and radiotherapy. However, chemo-resistance arises as a big obstacle in treating NPC. Therefore, there is a great need to develop new compounds that could reverse tumor drug resistance. In this study, eight matrine derivatives containing thiophene group were designed and synthesized. Structures of these 8 compounds were characterized by 1H-NMR, 13C-NMR, and high-resolution mass spectrometer (HRMS). The cytotoxicity and preliminary synergistic effects of these 8 compounds were detected against nasopharyngeal carcinoma (NPC) cells and cisplatin-resistant NPC cells (CNE2/CDDP), respectively. Furthermore, the in vivo and in vitro tumor resistance reversal effects of compound 3f were evaluated. Moreover, docking studies were performed in Bclw (2Y6W). The results displayed that compound 3f showed synergistic inhibitory effects with cisplatin against CNE2/CDDP cells proliferation via apoptosis induction. Docking results revealed that compound 3f may exert its effects via inhibiting anti-apoptosis protein Bcl-w.